Citogenetske preiskave pri slovenskih bolnikih z akutno levkemijo - Podgornik, Helena (Zdravniški vestnik, 2008)
Background Modern therapeutic concepts in acute leukemia are based on individual risk stratification at diagnosis and during follow-up. Cytogeneticsplays a central role for classification and for prognostication inacute myeloid (AML) and considering t(9;22) determination also in acute lymphoblastic leukemia (ALL). This method also helps to determine a suitable genetic marker for later monitoring of minimal residual disease (MRD). Resultsof standard cytogenetics obtained in our laboratory were analyzed and compared with literature data. Methods During the last two years cytogenetic analysis was done in 120 adults and children who were diagnosed with acute leukemia. Bone marrow cells were short-time cultivated to obtain metaphases which were analyzed after G-banding (Giemsa-trypsin). In majority of cases fluorescent in situ hybridization (FISH) was also applied to determine or confirm the suspected chromosomal aberrations. Results The standard cytogenetics was successful in 90% of samples. In 70% of AL patients clonal chromosomal changes were found. Recurrent chromosomal aberrations were determined with expected frequency as previously published for other populations. Also the frequencies of patients with a normal karyotype and complex chromosomal changes were in the expected range. Conclusions Using molecular cytogenetic and genetic methods a possibility that some of chromosomal changes were overlooked was considerably minimized. On the basis of the analyzed data we can be confident that the cytogenetic diagnostic approach in our acute leukemia patients is in accordance with international guidelines.
Keywords: Chromosome Aberrations; citodiagnostika; Citogenetika; Cytogenetics; diagnostika; Genetics; hematologija; In situ hibridizacija fluorescenčna; In Situ Hybridization, Fluorescence; Kromosomske aberacije; Leukemia, Myelocytic, Acute; levkemija; Levkemija mielocitna, akutna